2012
DOI: 10.5603/19754
|View full text |Cite
|
Sign up to set email alerts
|

Use of X-ray microprobe to diagnose bone tissue demineralization after caffeine administration

Abstract: Caffeine is a methylxanthine which permeates the placenta. In studies on animals, it has been shown to produce teratogenic and embryotoxic effects in large doses. The objective of this study was to assess the influence of caffeine on the development of bone tissue, with particular reference to elemental bone composition using an X-ray microprobe. The research was conducted on rats. The fertilized females were randomly divided into an experimental and a control group. The experimental group was given caffeine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…A tendency to worsen bone was also observed in old ovariectomized rats [ 31 ]. In most of those studies [ 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] caffeine was administered in higher doses than that used in the present study; in the rest of the cited studies [ 27 , 28 , 29 , 31 ], unfavorable effects of caffeine administered with the diet at doses of 10 or 20 mg/kg body weight were demonstrated. In our study, caffeine was administered once daily.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…A tendency to worsen bone was also observed in old ovariectomized rats [ 31 ]. In most of those studies [ 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] caffeine was administered in higher doses than that used in the present study; in the rest of the cited studies [ 27 , 28 , 29 , 31 ], unfavorable effects of caffeine administered with the diet at doses of 10 or 20 mg/kg body weight were demonstrated. In our study, caffeine was administered once daily.…”
Section: Discussionmentioning
confidence: 74%
“…Data on the effect of caffeine on bone in experimental conditions are inconsistent. Although the majority of previously published reports on the studies of caffeine administered at different doses for various periods of time to rats demonstrated rather its adverse skeletal effects [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], we have shown that caffeine administration at a moderate dose of 20 mg/kg per os (p.o.) once daily (by oral gavage) slightly counteracted the development of osteoporosis induced by estrogen deficiency [ 25 ].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…So far, experimental in vivo studies on the skeletal effects of caffeine indicated the deleterious effects of caffeine on prenatal development , and bones of young, rapidly growing rats or pregnant rats , as well as bone healing . A tendency to impair bone parameters was also found in old ovariectomized rats .…”
Section: Discussionmentioning
confidence: 99%
“…The implication in the acetylcholine-based neurotransmission is plausibly verified [25]. Caffeine regulatory potency in the body is an object of extensive research, and some of the caffeine related pathways probably remain unrevealed [26]. The present paper describes the search on caffeine potency to modulate the activity of cholinesterases, a crucial part of the cholinergic system.…”
Section: Introductionmentioning
confidence: 97%